Simulation of a single-phase active power filter based ANN controller - Mahadan, Mohd Ezwan (2013)
This project presents the employment of a single-phase active power filter (APF) to compensate harmonics generated by battery charger. The presence of the harmonics leads to various problems and poor power quality. The objectives of this project are to reduce the harmonic distortion and improve the power factor of the single-phase system with battery charger load. The operation of APF is verified using the simulations in Matlab/Simulink. Artificial neural network (ANN) control based shunt APF is compared to proportional-integral (PI) controller in order to regulate the DC-bus voltage and hysteresis current controller is employed to generate signal for switching purpose. The process is based on sensing line voltages, line currents, filter currents and DC side capacitor voltage. The error signal caused by the filter has been computed firstly. Then this error signal has been compensated using the controller and generates reference line current. The reference filter currents signal then obtained by subtracts the reference line current with the load current. This reference filter current is feed to the hysteresis current controller and compare with the sensed filter currents to obtain the switching signal for active power filter. Simulation results show that the ANN controller based shunt APF has better performance which has reduced harmonic distortion and improve system performance compared to the use of conventional PI controller. Keywords: Shunt APF, PI controller, ANN controller, Total Harmonic Distortion (THD)